a funçao definida por F (x)= x²-7x +10
a) F (o)=
b) F (2)=
c) F (1 )=
(2)
d) F ( -5)=
e) F (-3)=
Soluções para a tarefa
Respondido por
13
É substituir o valor na função.
f(x) = x² - 7x + 10
a) f(0)
0² - 7·0 + 10
f(0) = 10
b) f(2)
2² - 7·2 + 10
f(2) = 0
c) f(1)
1² - 7·1 + 10
f(1) = 4
2)
d) f(-5)
(-5)² - 7·(-5) + 10
f(-5) = 25 + 35 + 10= 70
e) f(-3)
(-3)² - 7·(-3) + 10
f(-3) = 9 + 28 + 10 = 40
f(x) = x² - 7x + 10
a) f(0)
0² - 7·0 + 10
f(0) = 10
b) f(2)
2² - 7·2 + 10
f(2) = 0
c) f(1)
1² - 7·1 + 10
f(1) = 4
2)
d) f(-5)
(-5)² - 7·(-5) + 10
f(-5) = 25 + 35 + 10= 70
e) f(-3)
(-3)² - 7·(-3) + 10
f(-3) = 9 + 28 + 10 = 40
Perguntas interessantes